Brine Shrimp Lethality Test (BSLT) of 96% Ethanol Extract of Ande-ande Lumut (Selaginella doederleineii) Leaves - Difa Prasticha, Yunita; Surahmaida (Biospecies, 2024)
Selaginella doederleineii is a fern plant that is efficacious for treating coughs, pneumonia and broken bones. Leaves are the primary medicinal parts. However, there has been no research regarding the toxicity of Selaginella doederleineii leaves. This study aims to evaluate potential toxicity of 96% ethanol extract of Selaginella doederleineii leaves against shrimp larvae (Artemia salina Leach) using the Brine Shrimp Lethality Test (BSLT) method. The toxicity value is shown by the LC50 value. This research method includes the extraction stage, larvae hatching stage, stock solutions and concentration dilutions of the extract preparation, toxicity test and LC50 value calculation. The toxicity test using 10 Artemia salina shrimp larvae were exposed to each test concentration (0 ppm, 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm) in triplicate. Larval mortality was assessed after 24 hours to calculate mortality percentage and LC50. The results showed that the LC50 value for the 96% ethanol extract of Selaginella doederleineii was 12.0221 ppm, indicating very toxic. It can be concluded that Selaginella doederleineii leaves exhibits significat toxicity to brine shrimp and potential to be developed as a raw material for anti-cancer drugs.